Complement activated granulocytes can cause autologous tissue destruction in man - E. Löhde; H. Raude; M. Lück; E. Kraas; W. Lierse (Hindawi Limited, 1992)
Activation of polymorphonuclear granulocytes (PMNs) by C5a is thought to be important in the pathogenesis of multiple organ failure during sepsis and after trauma. In our experiment exposure of human PMNs to autologous zymosan activated plasma (ZAP) leads to a rapid increase in chemiluminescence. Heating the ZAP at 56°C for 30 min did not alter the changes, while untreated plasma induced only baseline activity. The respiratory burst could be completely abolished by decomplementation and preincubation with rabbit antihuman C5a antibodies. Observation of human omentum using electron microscopy showed intravascular aggregation of PMNs, with capillary thrombosis and diapedesis of the cells through endothelial junctions 90 s after exposure to ZAP. PMNs caused disruption of connections between the mesothelial cells. After 4 min the mesothelium was completely destroyed, and connective tissue and fat cells exposed. Native plasma and minimum essential medium did not induce any morphological changes. These data support the concept that C5a activated PMNs can cause endothelial and mesothelial damage in man. Even though a causal relationship between anaphylatoxins and organ failure cannot be proved by these experiments C5a seems to be an important mediator in the pathogenesis of changes induced by severe sepsis and trauma in man.